Emerging Adults' Relationship with Caregivers and their Romantic Attachment: Quality Communication Helps. - Luerssen, Anna; Shane, Jacob; Budescu, Mia (Journal of Child & Family Studies, 2019)
Objectives: Caregivers play an influential role in their child's romantic attachment representations in emerging adulthood. In the current research, we explored one possible mechanism underlying this connection, the quality of caregiver-child communication about romantic relationships as indexed by emerging adults' perceptions of the frequency, comfortableness, and helpfulness of these conversations with their female caregiver. Methods: Survey data from a sample of emerging adults enrolled in an American university were analyzed with structural equation modeling to evaluate this mediational prediction using causal steps and bootstrapping of indirect effects approaches. Results: A higher quality caregiver-child relationship (higher support, less strain) was associated with higher quality communication about romantic relationships, and this communication was associated with lower attachment anxiety (indirect effect from support: β = −0.085; 95% CI [−0.139, −0.036], p = 0.001; indirect from strain: β = 0.020; 95% CI [0.005, 0.040], p = 0.026) and attachment avoidance (indirect effect from support: β = −0.094; 95% CI [−0.151, −0.043], p = 0.001; indirect effect from strain: β = 0.022; 95% CI [0.006, 0.043], p = 0.021). Fit statistics and indirect effects for the hypothesized model were compared and found superior to a variety of alternative models. Conclusions: The quality of emerging adults' conversations with their female caregiver about romantic relationships mediated the relationship between caregiver-child relationship quality and romantic attachment representations. Results are discussed in terms of the importance of romantic relationships and romantic attachment and the connection between the caregiver-child relationship and these outcomes in emerging adulthood.